OSTRACODA FROM SUBSURFACE SEDIMENTS OF KARIMATA STRAIT AS INDICATOR OF ENVIRONMENTAL CHANGES - Kresna Tri Dewi; Riza Rahardiawan (BULLETIN OF THE MARINE GEOLOGY, 2014)
Karimata Strait is a part of Sunda Shelf connected South China Sea with Malacca Strait, Indian Ocean and Java Sea. This shelf was a large Sunda Land that has been detected by many evidences as records of various paleo-environments. The purpose of this study is to recognize the characteristic community of ostracoda related to the environmental history of this shelf. Three selected cores sediments represented east (A), middle (B) and west (C) parts of Karimata Strait were used for Ostracoda based on standard method on micropaleontology. Additional method was applied of SEM-EDX analysis to abnormal specimens. The result shows that there are 43 species of ostracoda belonging to 34 genera identified in the study area. The highest number of ostracoda is found in Core B, in the middle part of the strait, and the lowest value belongs to the Core A that close to the land of Kalimantan. Several genera of Ostracoda were documented in all cores: Actinocythereis, Cytherella, Cytherelloidea, Keijia, Keijella, Hemicytheridea, Hemikrithe, Neocytheretta, Neomonoceratina, Loxoconcha, Pistocythereis, Stigmatocythere and Xestoleberis. Vertically, ostracoda are mostly found in the upper part of the cores and decrease or disappear in the lower part of Cores A and C where dominated by black organic materials. It may relate to a wide swampy area before the last sea level rise as part of the history of the SundaShelf about 15,000 years ago. Some major elements (C, CaO, Al2O4, FeO, SiO2, MgOdan SO3 covered or filled abnormal specimens that can provide additional information about environmental changes in the study area, such as Carbon may relate to charcoal from land of Kalimatan and Sumatera Keywords: Ostracoda, subsurface sediment, EDX, environmental changes, Karimata Strait Selat Karimata merupakan bagian dari Paparan Sunda menghubungkan Laut China Selatan dengan Selat Malaka, Samudera Hindia, dan Laut Jawa. Paparan ini merupakan sebuah Dataran Sunda yang luas yang terdeteksi dari bukti-bukti sebagai rekaman berbagai lingkungan purba.Tujuan dari studi ini adalah untuk mengetahui karakteristik komunitas ostracoda berkaitan dengan sejarah lingkungan paparan ini. Terpilih tiga sedimen pemercontoh inti mewakili bagian timur (A), tengah (B) dan barat (C) Selat Karimata digunakan untuk studi Ostracoda berdasarkan metoda standar pada mikropaleontologi. Metoda tambahan adalah aplikasi SEM-EDX terhadap spesimen abnormal. Hasil menunjukkan bahwa di daerah penelitian teridentifikasi 43 spesies ostracoda termasuk dalam 34 genera. Jumlah ostracoda tertinggi ditemukan di Core B dari bagian tengah selat dan terendah di Core A yang berdekatan dengan daratan Kalimantan. Beberapa genera ostracoda ditemukan di semua sampel: Actinocythereis, Cytherella, Cytherelloidea, Keijia, Keijella, Hemicytheridea, Hemikrithe, Neocytheretta, Neomonoceratina, Loxoconcha, Pistocythereis, Stigmatocythere dan Xestoleberis. Secara vertikal, ostracoda umumnya ditemukan di bagian atas dari core dan menurun atau menghilang di bagian bawah Core A dan C yang di dominasi oleh material organik berwarna hitam. Hal ini kemungkinan berkaitan dengan daerah rawa yang luas dan sebelum muka laut naik terakhir pada sejarah Paparan Sunda sekitar 15.000 tahun yang lalu. Beberapa zat kimia (C, CaO, Al2O3, FeO, SiO2, MgO dan SO3) menutupi atau mengisi spesimen abnormal dapat memberi informasi tambahan tentang perubahan lingkungan di daerah penelitian, seperti karbon mungkin berkaitan dengan arang dari daratan Kalimantan dan Sumatera. Kata kunci: Ostracoda, sedimen bawah dasar laut, EDX, perubahan lingkungan, Selat Karimat